Semidistributed Hydrological Model with Scarce Information: Application to a Large South American Binational Basin - Oñate Valdivieso, F. (2013)
In this paper the process to implement the Soil and Water Assessment Tool (SWAT) in Catamayo-Chira binational basin (11,910.74 km2) in the border area between Ecuador and Peru (South America) is detailed. The basin under study has a low density of meteorological and hydrological stations as well as a notable variation in its biophysical characteristics, which further highlights the lack of information. The SWAT model requires a great amount of parameters for its implementation. Its performance was studied, even though the writers had scarce information. The SWAT model made a relatively satisfactory reproduction of the historical record of flows, i.e., Nash-Sutcliffe model efficiency coefficient of 0.73, with certain limitations in calculation of sediment production. Two land-use scenarios were analyzed, observing that an increase of natural forest and shrub areas could significantly reduce sediment production.